The Use of 'Woman/Female' and 'Man/Male' as a Specific Gender Markers in Albanian Language in Light of Society Changes - Paçarizi, Rrahman (The journal of language and linguistic studies, 2021)
Gender issues in Languages are very sensitive and interesting, especially in the societies making effort to empower the presence and the role of women in respective society. Kosovar society is one of the examples of such efforts and debates initiated by women's rights groups and organizations. The situation has changed rapidly in some senses of the use of different linguistics markers regarding the use of respective terms that are considered more appropriate or politically correct than the traditional ones. For example, the terms 'gender' and 'sex' are alternating each-other, not only to denote biological distinctions but also cultural ones. The most rapid changes have been noticed in the use of the term 'woman' instead of the traditional term 'female', which in the perception of the average speakers was not an offensive term for women. But, there is still in use the term 'female' to denote the person of certain gender or sex, especially in informal and social use and in instant messaging. One of the issues identified during the monitoring of media for this paper, was the use of masculine plural to cover also the feminine members of certain groups, especially while naming occupations and this situation is unavoidable because the gender in Albanian has clear grammatical features in the plural as well. To complete this research, I monitored media in different formats (newspapers, online media, social media, radio, and television, in Albanian, Serbian and Macedonian), and also I did a focus group with youngsters on instant messaging platforms.